Ocena siły mięśniowej i zakresów ruchów stawów obręczy barkowej i odcinka szyjnego kręgosłupa u osób po laryngektomii - Kaźmierczak, Urszula; Zniszczol, Paweł; Kropkowska, Patrycja; Goch, Aleksander; Radzimińska, Agnieszka; Strojek, Katarzyna; Weber-Rajek, Magdalena; Kędzierski, Andrzej; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Kaźmierczak Urszula, Zniszczol Paweł, Kropkowska Patrycja, Goch Aleksander, Radzimińska Agnieszka, Strojek Katarzyna, Weber-Rajek Magdalena, Kędzierski Andrzej, Zukow Walery. Ocena siły mięśniowej i zakresów ruchów stawów obręczy barkowej i odcinka szyjnego kręgosłupa u osób po laryngektomii = Evaluation of muscle strength and range of movement in the joints of the shoulder girdle and the cervical spine in patients after laryngectomy. Journal of Education, Health and Sport. 2015;5(11):25-42. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33164 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A25-42 https://pbn.nauka.gov.pl/works/665740 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. Ocena siły mięśniowej i zakresów ruchów stawów obręczy barkowej i odcinka szyjnego kręgosłupa u osób po laryngektomii Evaluation of muscle strength and range of movement in the joints of the shoulder girdle and the cervical spine in patients after laryngectomy Kaźmierczak Urszula1, Zniszczol Paweł1, Kropkowska Patrycja1, Goch Aleksander1, Radzimińska Agnieszka1, Strojek Katarzyna1, Weber-Rajek Magdalena1, Kędzierski Andrzej2, Zukow Walery3 1Katedra Fizjoterapii , Zakład Kinezyterapii i Masażu Leczniczego, Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy 2Zakład Mechaniki Kwantowej, Instytut Fizyki, Uniwersytet Mikołaja Kopernika w Toruniu 3Instytut Kultury Fizycznej, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: laryngektomia, pomiar siły mięśniowej, pomiar zakresów ruchu, obręcz barkowa, odcinek szyjny kręgosłupa. Key words: laryngectomy, the measurement of muscle strength, range of movement measurement, shoulder girdle, cervical spine. Streszczenie Krtań od góry graniczy z gardłem dolnym, a od dołu przechodzi w tchawicę, znajdując się w szyi na wysokości V – Vi kręgu szyjnego spełniając funkcję ochronną dróg oddechowych, oddechową i głosową. Rak krtani jest najczęściej występującym nowotworem złośliwym w obrębie głowy i szyi. Leczenie polega na przeprowadzeniu operacji (laryngektomii) i wspomagającej radioterapii. Zabieg laryngektomii całkowitej usuwa wiele struktur z szyi (mięśnie, tkanki miękkie, nerwy i węzły chłonne). Wpływa to na ruchomość i siłę mięśniową odcinka szyjnego kręgosłupa i głowy oraz obręczy barkowej. Badanie przeprowadzono u 31 osób laryngektomowanych, spotykających się w klubie „Orion” w Bydgoszczy. Średnia wieku wynosiła 66,5. Grupę kontrolną stanowiły osoby zdrowe, bez ograniczeń ruchomości w odcinku szyjnym kręgosłupa i obręczy barkowej. Badanie polegało na pomiarze siły według skali Lovetta w odpowiednich pozycjach oraz pomiarze za pomocą miary krawieckiej ruchomości odcinka szyjnego kręgosłupa i obręczy barkowej za pomocą goniometru. Laryngektomia wpływa niekorzystnie na siłę mięśniową i zakresy ruchomości szczególnie u osób, u których usunięto węzły chłonne w okolicy szyi. Abstract Larynx from top borders the bottleneck, and from the bottom of the passes in the trachea, in the neck at a height of V-Vi cervical vertebra fulfilling a protective function respiratory tract, and voicemail. Laryngeal cancer is the most common malignant tumor in the head and neck. Treatment consists of an operation (laryngectomy) and supportive radiotherapy. Total laryngectomy treatment removes many of the neck structures (muscles, soft tissues, nerves and lymph nodes). This affects mobility and muscle strength of the cervical spine and head and shoulder girdle. The study was conducted on 31 patients had laryngectomies, meeting in the Club "Orion" in Bydgoszcz. The average age amounted to 66.5. The control group were healthy people, without the limitations of movable property in the cervical spine and shoulder girdle. Study on the measurement of the strength of Lovett scale under the appropriate headings and measured with a measuring tape mobility of the cervical spine and shoulder girdle using a goniometer. Laryngectomy adversely affects muscle strength and range of mobility especially in people who have been removed lymph nodes in the neck area.